Observed cave flow behaviour at the Argyle block cave and its implications for cave performance - van As, A.; Van Hout, G.; Ooi, J.; Wilson, M. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Argyle Diamond Mine (ADM) block cave was the first cave mine to deploy a cave-scale active Cave Tracker System, complemented by passive flow markers and surface observations. These marker systems were installed to better understand cave flow behaviour in a geologically complex orebody, and to assess the practical requirements and limitations associated with cave flow monitoring technologies so that they could be successfully deployed at the Oyu Tolgoi block cave mine. This paper documents the installation approaches, operational performance, and data recovery of the Cave Tracker System and associated flow markers implemented at ADM. The cave tracker results, recovered markers, and surface breakthrough observations collectively indicated a predominantly isolated draw behaviour, characterised by limited lateral interaction between adjacent drawpoints. Notable examples included beacons exhibiting strongly channelised vertical movement consistent with tight drawcone formation, while others demonstrated significant lateral displacement, potentially indicative of rilling mechanisms within the caved column. These observations provided direct insight into cave flow processes and highlighted the sensitivity of cave behaviour to draw strategy and cave geometry. The ADM experience offers an important early reference case for cave flow monitoring, demonstrating how integrated flow measurements can be used to improve interpretation of cave mechanics and to inform draw management strategies in future large-scale block cave operations.